Using Augmented Reality and Modified Schema-Based Instruction to Teach Problem Solving to Students With Autism - Root, Jenny R.; Cox, Sarah K.; Davis, Kathryn; Gonzales, Sarah (Remedial and special education, 2022)
Young adults with autism spectrum disorder (ASD) need both academic and social skills required to apply acquired knowledge and skills in real-world settings. This study evaluated the effects of a multicomponent intervention incorporating both Modified Schema-Based Instruction (MSBI) and video-based instruction delivered via augmented reality (AR) to teach the social and mathematical problem-solving skills needed to execute personal finance tasks in the community. Participants were four 21-year-old young adults with ASD enrolled in a public school transition program located on the campus of a technical college. Findings of the single-case multiple probe across participant design support a functional relationship between the multicomponent treatment package and the social and mathematical problem-solving skills of the young adults with ASD. Furthermore, participants were also able to self-correct errors after watching AR-triggered model videos. Generalization to a novel setting was tested. Results, implications, and suggestions for future research are discussed